Algoritma C4.5 Dalam Mengklasifikasi Tindak Kejahatan Yang Sering Terjadi Di Kecamatan Siantar Barat Pematangsiantar - Soleh, Muhammad; Andani, Sundari Retno; Qurniawan, Hendry (TIN: Terapan Informatika Nusantara, 2021)
Crime is a problem that often occurs in everyday life and is an action that can cause certain parties to be harmed both physically and materially. Factors that influence these crimes include immorality, molestation, theft, gambling, extortion/threatening, embezzlement, fraud, and vandalism. The increase in crime at this time is very significant. Over time, crime increased in an erratic pattern. In this study, the authors tried to mine data (data mining) reports of crimes that occurred at the Siantar Barat Police, Pematangsiantar City from the previous year. The data were analyzed using the C.45 algorithm, where this algorithm aims to classify data on certain crime classes. With the creation of this system, it is hoped that it can assist the police in classifying crimes and minimizing areas prone to crime